Physico-chemical and Bacterialogical Analyses of Sachet water samples in Abeokuta Metropolis - Taiwo A.A; Idowu Oluwadare; Lanre-Iyanda Y.A; Jolaoso A.A; Jiboku O.O; T.O, Ijaola; Taiwo A.G (Global Journal of Food and Agribusiness Management, 2020)
Sachet water samples were purchased from 26 different wholesale depots in Abeokuta, Physico-chemicals and bacteriological analyses were carried out on them to ascertain their wholesomeness using standard methods . Results obtained showed a consistent pH range of 6.00-7.87 for all samples, Total Solids (TS) were between 25.00mg/L -187.5mg/L, Total Dissolved Solids (TDS) (26.20mg/L-122.20mg/L), Acidity (0.10-0.80mg/L), Total hardness (2.00mg/L-43.00mg/L) and Conductivity (35.00µS/cm) -257.00µS/cm). 96.15% of the samples had acceptable world Health Organisation values of <10CFU/ml while 100% of the sample had acceptable Coliform or Escharichia coli values of <10CFU/ml (WHO,1999) . The results showed that an effective quality control system and a high level of sanitation in all the production depots.